Studies on the Performance of Phillipines and Malaysian Provenances of Albizia falcataria (L.) Forberg at Nursery Stage Under North Indian Moist Tropical Condition - Bahuguna, V. K.; Unnikrishnan, K. P.; Dhaundiyal, U. C. (Indian Forester, 1989)
Albizia falcataria (L.) Forberg is one of the most fast growing species. It makes few demands on the soil and hence is suitable for rapid afforestation of poor soil. On account of its wide adaptability, the species promises to be one of the excellent planting materials for social forestry and wasteland afforestation programmes, particularly in areas where the rainfall is good. The paper deals with the results of an experiment, carried out on its nursery technique and choice of better provenance under Dehra Dun conditions.